Evaluating corn and corn gluten feed in growing cattle diets as a replacement for roughage - N.G. Whitham; C.M. Coetzer; R.D. Hunter; James S. Drouillard; Dale A. Blasi; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1999)
A 99-day study was conducted to evaluate growth performance of 216 beef heifers (average 524 lb) fed traditional roughage-based diets at 2.75% of body weight or limit-fed highconcentrate diets containing corn or corn gluten feed fed at 2.0% of body weight. Dietary treatments included roughage plus corn, roughage plus corn gluten feed, limit-fed corn, limitfed corn with added Smartamine®-ML (providing 10 g/day ruminally protected lysine), limitfed corn gluten feed, and limit-fed corn gluten feed with added Smartamine. Adding Smartamine-ML to the diet did not improve performance significantly compared to unsupplemented groups (P>.30). Limit-fed diets containing corn and corn gluten feed resulted in more efficient growth than the respective roughage-based treatments (P<.01). Limit-fed gluten feed diets resulted in gains that were approximately 88% of that with the cornbased diets. Performance was not different for corn and corn gluten feed when added to roughage-based diets.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Corn gluten feed; Smartamine-ML; Growing cattle; Growth